2001
DOI: 10.1107/s0907444901008642
|View full text |Cite
|
Sign up to set email alerts
|

The structure and domain organization ofEscherichia coliisocitrate lyase

Abstract: Enzymes of the glyoxylate-bypass pathway are potential targets for the control of many human diseases caused by such pathogens as Mycobacteria and Leishmania. Isocitrate lyase catalyses the first committed step in this pathway and the structure of this tetrameric enzyme from Escherichia coli has been determined at 2.1 A resolution. E. coli isocitrate lyase, like the enzyme from other prokaryotes, is located in the cytoplasm, whereas in plants, protozoa, algae and fungi this enzyme is found localized in glyoxys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…The molecular modelling of CmICL revealed that the Gln207 of CmICL is present in the barrel fold, and its side chain is directed toward the inner space of the barrel (Fig. 7), in the same way as the His184 of EcICL (Britton et al, 2000(Britton et al, , 2001Sharma et al, 2000). It has been reported that four EcICL mutants, in which His184 was replaced by Leu, Lys, Arg or Gln, are not able to form the tertiary structure, and that only the H184Q mutant shows activity (0?28 % of the wild-type EcICL activity; Diehl & McFadden, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The molecular modelling of CmICL revealed that the Gln207 of CmICL is present in the barrel fold, and its side chain is directed toward the inner space of the barrel (Fig. 7), in the same way as the His184 of EcICL (Britton et al, 2000(Britton et al, , 2001Sharma et al, 2000). It has been reported that four EcICL mutants, in which His184 was replaced by Leu, Lys, Arg or Gln, are not able to form the tertiary structure, and that only the H184Q mutant shows activity (0?28 % of the wild-type EcICL activity; Diehl & McFadden, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…1a). Lys194 of EcICL should be essential for the catalytic function, because an 'active-site loop' including this residue moves flexibly when the enzyme binds to the substrate and releases the reaction products (Britton et al, 2000(Britton et al, , 2001Sharma et al, 2000;cf. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these enzymes catalyze the transformation of an α-oxocarboxylate substrate via an oxyanion intermediate and/or transition state (Figure 1) with the aid of a Mg 2+ cofactor. Structure determinations have been carried out for each of these enzymes, with the exception of carboxyPEP mutase and oxaloacetate hydrolase, to define a conserved catalytic scaffold located at the C-terminal edge of the main-frame α/β-barrel (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The catalytic scaffold provides a binding pocket for the α-oxocarboxylate substrate that includes residues engaged in hydrogen bond formation with the carboxylate substituent, and residues that bind the Mg 2+ cofactor directly or via water molecules.…”
mentioning
confidence: 99%